Involvement of DNMT 3B promotes epithelial-mesenchymal transition and gene expression profile of invasive head and neck squamous cell carcinomas cell lines. Issue 1 (December 2016) - Chen, Li-Hsuen; Hsu, Wen-Lin; Tseng, Yen-Ju; Liu, Dai-Wei; Weng, Ching-Feng
Abstract Background The 5-year overall survival rates for head and neck cancer (HNC) relies on distant metastasis. Importantly, the epithelial-mesenchymal transition (EMT) is believed to be an initial step of metastasis. However, the relationship of epigenetic with EMT formation is still unexplored in HNC. This study focuses on invasive subclones of HNC cell lines through the simulation of invasion in vitro; and underlying mechanisms were analyzed including DNA methylation and gene expression profile. Methods Invasive subclones of NHC cell lines were successfully obtained using transwell coated with Matrixgel. Cells invaded through 8 μm pore several times were subcultured and examined with EMT features including morphology, EMT marker genes expression, and invasive ability. Moreover, compared the profile of genes expression in parental and invasive cells was analyzed using mRNA expression array. Results DNA methyltransferase 3B (DNMT 3B) was upregulated in invasive subclones and might control the 5′ region of E-cadherin (E-cad) methylation and further inhibited E-cad protein expression. Interference of DNMT 3B by siRNA or miRNA 29b could reduce EMT and cell invasion. Expression array analysis revealed the most possible involved pathways in cell invasion including arginine and proline metabolism, TGF-beta, and focal adhesion. Conclusions DNMT 3B might control EMT by DNA methylation manner in invasive HNC cell lines. Moreover, miR-29b mimic downregulated DNMT 3B and inhibited EMT and cell invasion indicated the role of therapeutic agent for invasive HNC. Genes identified from array data and new molecules are involved in metastasis of HNC need further validation.